Granzyme K+CD8+ T cells interact with fibroblasts to promote neutrophilic inflammation in nasal polyps - Cui-Lian Guo; Chong-Shu Wang; Zhi-Chao Wang; Fei-Fan Liu; Lin Liu; Yang Yang; Xia Li; Bei Guo; Ruo-Yu Lu; Bo Liao; Jin-Xin Liu; Hai Wang; et al. (Nature Communications)
Abstract Sophisticated interactions between stromal and immune cells play crucial roles in various biological and pathological processes. In chronic rhinosinusitis with nasal polyps (CRSwNP), the upper airway inflammation in many patients is driven by TH2, ILC2, and eosinophils, thus being treated with glucocorticoids and anti-type 2 inflammation biologics. The resistance to these therapies is often associated with neutrophilic inflammation, which has also been widely identified in CRSwNP, but the underlying mechanisms remain unclear. Using single-cell analysis, spatial transcriptomics, and T-cell receptor sequencing, we identify an increased presence of granzyme K+(GZMK+) CD8+ T cells in NPs, which possess a phenotype distinct from the cytotoxic GZMB+ effector CD8+ T subset. GZMK+CD8+ T cells are found to express CXCR4 and interact with CXCL12-secreting fibroblasts, inducing the latter to produce neutrophil chemoattractants in a manner uniquely mediated by GZMK but not other granzymes. This GZMK+CD8+ T cell-fibroblast crosstalk is also observed in other inflammatory diseases. Furthermore, GZMK+CD8+ T cells exhibit a selective expansion of clones that recognize Epstein-Barr virus. Here, we show that GZMK marks a phenotypically distinct subset of effector CD8+ T cells that promote neutrophilic inflammation.